Seismic behavior of shear walls with boundary CFST columns and embedded multiple steel plates: Experimental investigation. (1st April 2018) - Qiao, Qi-Yun; Cao, Wan-Lin; Li, Xiang-Yu; Dong, Hong-Ying; Zhang, Wen-Wen; Yin, Fei
Highlights: An innovative composite shear wall with boundary CFST columns and embedded multiple steel plates has been developed. Seven composite shear wall specimens are investigated by cyclic loading tests. The failure characteristics and seismic behavior of the shear walls are investigated. Retrofitting for the specimens are carried out and the behavior of the specimens after retrofitting are investigated. Evaluation method for ultimate strength has been developed with adequate accuracy. Abstract: In this study, an innovative composite shear wall, comprised of boundary Concrete Filled Steel Tubular (CFST) columns, and Reinforced Concrete (RC) walls embedded with multiple steel plates has been developed. Seven specimens were investigated by cyclic loading tests. The parameters were the type of the boundary CFST columns, the number of multiple steel plates and the axial force ratio. There were two loading stages for the tests. During stage 1, the specimens were tested until a 2.0% drift ratio was attained. After stage 1, damaged specimens were retrofitted and tested in stage 2. The failure characteristics, hysteretic behavior, strength and deformation, strains, energy dissipation capacity and stiffness were studied. The results show that the hysteresis curves of the innovative shear walls were stable. The embedded multiple steel plates had a considerable effect on the seismic behavior of the innovative shear walls, and the strength increased with increasing number of steel plates. There was no considerable difference in the effect on seismic behavior for the different types of the boundary CFST columns. The developed shear walls, after retrofitting, were shown to satisfy seismic requirements. Finally, an evaluation method for the ultimate strength of the shear walls was developed with adequate accuracy.